2015
DOI: 10.1118/1.4926554
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of tumor response to radiation and vascular targeting therapy in mice using quantitative ultrasound spectroscopy

Abstract: Results from QUS analysis presented in this study confirm that acute tumor response is linked to a vascular effect following high doses of radiation therapy. Overall, this is in agreement with previous reports suggesting that acute tumor radiation response is regulated by a vascular-driven response. Data also suggest that Sunitinib may enhance tumor radiosensitivity through a vascular remodeling process, and that QUS may be sensitive to changes in tissue properties associated with vascular remodeling. Finally,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 66 publications
0
11
0
Order By: Relevance
“…Other studies have begun to assess such factors using image-based texture analysis to account for tumor heterogeneity [44] . Other studies have demonstrated recently also the effect of tumor vascularity on QUS parameters [45] .…”
Section: Discussionmentioning
confidence: 89%
“…Other studies have begun to assess such factors using image-based texture analysis to account for tumor heterogeneity [44] . Other studies have demonstrated recently also the effect of tumor vascularity on QUS parameters [45] .…”
Section: Discussionmentioning
confidence: 89%
“…Staining with ISEL was quantified by computing a ratio of ISEL stained areas to whole tumour cross-sectional area, resulting in a percent cell death index. This was carried-out using a custom MATLAB (The MathWorks, Natick, MA) routine, which allows the user to compute the number of brown pixels (ISEL-stained) over the total number of pixels per whole segmented tumour cross-section in a digitized histology slide 7 , 27 , 31 . Endothelial-specific CD31 staining was used to quantify micro-vascular densities (MVD) and to complement power Doppler findings.…”
Section: Methodsmentioning
confidence: 99%
“…More specifically, volumetric power Doppler ultrasound was utilized to monitor tumour vascular responses in longitudinal studies 20 - 22 . Furthermore, power Doppler, quantitative ultrasound spectroscopy (QUS) methods were used to assess acute tumour responses to prescribed therapies 23 - 27 . In addition to ultrasound, we collected tumours post-mortem to assess cell death and micro-vascular densities using standard immunohistological methods (CD31 and ISEL).…”
Section: Introductionmentioning
confidence: 99%
“…Structural and morphological properties impact these parameters, which are related to the scatterer size (SI, SS), the acoustics scatterer concentration (MBF, SI), or difference in acoustic impedance between the scatterer and its surrounding medium (SI). Spatial parametric images of the MBF were generated by displaying the results of a sliding window analysis on a pixel-by-pixel basis within the ROI [ 17, 19, 20 ]. Statistical analysis was done with a multivariate model analysis and a one-way ANOVA as presented in Tables 1 and 2 .…”
Section: Methodsmentioning
confidence: 99%
“…Briefly, regions-of-interest (ROIs) were selected to encompass the MFP and exclude image artifacts and skin lines. A Fourier transform was applied to the RF data along each scan line within the ROI to obtain a power spectrum; spectra were averaged over all scan lines in the ROI and normalized to a reference phantom power spectrum [15][16][17][18][19][20]. Linear regression analysis was performed on each normalized power spectrum to generate a best-fit-line within a -6dB window to obtain MBF, SS, and SI parameters [15][16][17][18][19][20].…”
Section: Ultrasound Imaging and Qusmentioning
confidence: 99%